The Evaluation Of Sales Promotion In Jakarta Retail Business - Joseph M.J. Renwarin (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2019)
The occurrence of the gap phenomenon between Indonesia's economic growth and population has increased but the retail market has declined. Therefore, the purpose of research is to find out how much the relationship between sales promotions and customer satisfaction in Matahari stores. The research method uses a quantitative approach with accidental sampling method through the distribution of questionnaires to 100 retail customers. The result of this research is the relationship between sales promotion and increasing customer satisfaction. The management should focus on midnight sale and member membership because it has a significant impact on customer satisfaction. The voucher discount variable and buy two get one free have not significant on customer satisfaction. In the next future, the research focuses on the increase of online shore sales promotion.